Pengaruh Keselamatan dan Kesehatan Kerja terhadap Produktivitas Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Berjaya Group - Ardiani, Winda; Putra, Rizky; Hasibuan, Fira Alzira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is based on human resources which play a very important role in realizing the success of a company, including employees who are active assets requiring special attention from the company. In fact, employees as the main asset in the company, deserve intense attention and regular direction. Therefore, this study aims to describe the effect of occupational safety and health programs on employee productivity through job satisfaction as an intervening variable at PT. Berjaya Group with 126 people as a sample. The results obtained are Occupational Safety has a positive and significant effect on Job Satisfaction, Occupational Health has a positive and significant effect on Job Satisfaction, Occupational Safety has a positive and significant effect on Employee Productivity, Occupational Health has a positive and significant effect on Employee Productivity, Job Satisfaction has a positive and significant effect on Employee Productivity, Job Satisfaction significantly mediates the effect of Occupational Safety on Employee Productivity, Job Satisfaction significantly mediates the effect of Occupational Health on Employee Productivity. Keywords : Occupational Safety, Occupational Health, Job Satisfaction, Employee Productivity.